On (not) giving up: animals, biopolitics, and the impersonal in J.M. Coetzee's Disgrace. Issue 3 (15th April 2016) - Barney, Richard A.
Abstract : This article examines how David Lurie's peculiar inability to grasp his increasing intimacy with animals in J.M. Coetzee's Disgrace marks a significant departure from Coetzee's treatment of human–animal relations in other texts. If The Lives of Animals considers changing how human beings treat animals by focusing on rights, empathy, and the imagination oriented around 'the person' as individual subject, then Disgrace documents a strikingly different process via the 'impersonal', whereby an intermediary space between the personal and non-personal emerges in order to accommodate human and non-human animals alike. Lurie's curiously opaque experience can thus be accounted for, first, by Coetzee's career-long use of narrative strategies that displace the authority of the person as writer or character and, second, by recent discussions of the animal as a philosophical category by biopolitical analysts such as Roberto Esposito, who has staked out the impersonal as the most promising strategy for expanding the human political franchise. Extending Esposito's project to include animals themselves, this essay argues, can align it with Coetzee's portrayal of Lurie's transformation, while also offering ways to recast the problematic relation between Coetzee's stress on ethical responsibility and the prospect of political change in his work as a whole.